Synthesis, Characterizatiᴏn, and Bioactivity Assessment of Rh(III) and VO(IV) Complexes with Isatin Derivative N1,N2-bis(2-oxoindolin-3-ylidene)ethanebis(thioamide) - Ahmed, Yusra Jalil; Hasan, Shurooq Abdulfattah; Hamud, Waeel Mohammed; Mahmoud, Nawal Hamdan (Indonesian Journal of Chemistry, 2024)
The new two-component complexes of Rh(III) as well as VO(IV), with the base of Schiff ligand associated with the isatin derivative N1,N2-bis(2-oxoindolin-3-ylidene)ethanebis(thioamide) (L) were prepared by one-step method reaction between isatin compound and dithiooxamide by condensation in presence of glacial acetic acid and investigated through applying the FTIR, UV-vis devices, evaluation of carbon, hydrogen, nitrogen and halogens elements using elemental analysis, flame atomic absorption, magnetic susceptibility, molar conductivity, GC-MS, LC-MS, XRD, 1H and 13C-NMR. Depending on the results obtained from the measurement techniques, the structure of Rh(III) complex was octahedral geometry, while VO(IV) complex was square pyramidal geometry. The antibacterial property for the prepared Schiff-based ligand L and metallic complexes 1 and 2 in this research was examined towards two different kinds about pathological microbes growth of Escherichia coli and Staphylococcus aureus, respectively, in comparison with conventional antibiotic cephalexin.